Recapitulating Tumorigenesis in vitro: Opportunities and Challenges of 3D Bioprinting - Kronemberger, Gabriela S.; Miranda, Guilherme A. S. C.; Tavares, Renata S. N.; Montenegro, Bianca; Kopke, Úrsula de A.; Baptista, Leandra S. (Frontiers in Bioengineering and Biotechnology, 2021)
Cancer is considered one of the most predominant diseases in the world and one of the principal causes of mortality per year. The cellular and molecular mechanisms involved in the development and establishment of solid tumors can be defined as tumorigenesis. Recent technological advances in the 3D cell culture field have enabled the recapitulation of tumorigenesis in vitro, including the complexity of stromal microenvironment. The establishment of these 3D solid tumor models has a crucial role in personalized medicine and drug discovery. Recently, spheroids and organoids are being largely explored as 3D solid tumor models for recreating tumorigenesis in vitro. In spheroids, the solid tumor can be recreated from cancer cells, cancer stem cells, stromal and immune cell lineages. Organoids must be derived from tumor biopsies, including cancer and cancer stem cells. Both models are considered as a suitable model for drug assessment and high-throughput screening. The main advantages of 3D bioprinting are its ability to engineer complex and controllable 3D tissue models in a higher resolution. Although 3D bioprinting represents a promising technology, main challenges need to be addressed to improve the results in cancer research. The aim of this review is to explore 1) the principal cell components and extracellular matrix composition of solid tumor microenvironment; 2) the recapitulation of tumorigenesis in vitro using spheroids and organoids as 3D culture models and 3) the opportunities, challenges and applications of 3D bioprinting in this area.